Formulasi dan Evaluasi Salep Virgin Coconut Oil (VCO) - Lulu Hikmah Fauziah; Siti Haura Khairunnisa; Caecilia Sukma Larasati; Sofi Khoerunnisa; Dini Dwi Oktaviani; Feronika Evma Rahayu (STIKes Medistra Indonesia, 2026)
An ointment is a semisolid formulation with a smooth texture, minimal water content, and hydrophobic properties; it is used for direct application to the skin or mucous membranes, including the eye area. Virgin Coconut Oil (VCO) is pure coconut oil processed without the use of chemicals or organic solvents; it has low water and free fatty acid content, is clear in appearance, has a distinctive aroma, and functions as a natural emollient and antioxidant. This study aims to formulate and evaluate sterile VCO-based ointments at various concentrations: 0% (F0), 10% (F1), 20% (F2), and 30% (F3). The ingredients used include VCO as the active ingredient (0–30%), liquid paraffin as an emollient (10%), lanolin as an emollient and emulsion stabilizer (5%), chlorobutanol as a preservative (0.5%), white petrolatum as the main base (85%), and triethanolamine (TEA) to adjust the pH (1%). Evaluation of the formulations involved analysis of general physical properties, acidity level, spreadability, adhesion, solution viscosity, and mixture uniformity. The findings showed that all formulations were white to off-white in color, semi-solid in form, had a characteristic odor, and a consistent texture. The pH value for F0 was 5 (acidic), while the pH for F1 through F3 was 7 (neutral). The spreadability of F0 through F2 was 5 cm, whereas F3 reached 7 cm. The adhesion time for F0 was 5 seconds, while F1 through F3 had an adhesion time of 4 seconds. Viscosity ranges from 25,600 to 43,100 mPa·s. All these parameters meet pharmaceutical standards, including a spreadability of 5 to 7 cm, a minimum adhesion time of 4 seconds, and a viscosity range of 2,000 to 50,000 mPa·s. Formula 2 (20% VCO) was identified as the best formula because it has a neutral pH, spreadability and adhesion that meet the criteria, a sufficiently high viscosity of 35,500 mPa·s, and a uniform texture. In conclusion, it can be concluded that the addition of terpene-rich coconut oil at a concentration of 20% produces a contamination-free ointment with the most balanced physical characteristics.